Factors Influencing Women's Security in Society: Integrating Thematic Analysis and the Analytic Hierarchy Process with Emphasis on Social Well-being - Haji, Zeynab; Hashemianfar, Seyed Ali; Haghighatian, Mansour (Management Strategies and Engineering Sciences, 2024)
Background and Objective: This study investigates the factors influencing women's security in society using a framework of Thematic Analysis and the Analytic Hierarchy Process (AHP). By identifying and prioritizing these factors, the research contributes to the development of effective strategies to enhance the safety and well-being of women. This study adopted a mixed-method approach, combining Thematic Analysis with the Analytic Hierarchy Process. Thematic Analysis was utilized to identify key themes and patterns in the existing literature and empirical data related to women's security. Subsequently, the AHP methodology was employed to prioritize these factors based on expert judgments and pairwise comparisons. Thematic Analysis identified key dimensions of women's security, with socio-economic factors (relative importance = 0.195) ranking highest, followed by legal and political factors (relative importance = 0.183). Other significant factors included institutional factors (relative importance = 0.136), cultural and social norms (relative importance = 0.124), community and family dynamics (relative importance = 0.102), technology (relative importance = 0.083), environmental factors (relative importance = 0.074), political and conflict-related factors (relative importance = 0.052), and health and well-being factors (relative importance = 0.051). This study highlights the multifaceted nature of women's security and emphasizes the importance of addressing various factors comprehensively. By integrating Thematic Analysis with the AHP framework, the study provides valuable insights into understanding and addressing the complex challenges faced by women in society.